Cefiderocol for Extensively Drug-Resistant Gram-Negative Bacterial Infections: Real-world Experience From a Case Series and Review of the Literature. (21st May 2020) - Zingg, Sandra; Nicoletti, G Jacopo; Kuster, Sabine; Junker, Milena; Widmer, Andreas; Egli, Adrian; Hinic, Vladimira; Sendi, Parham; Battegay, Manuel; Bättig, Veronika; Khanna, Nina; Tschudin-Sutter, Sarah
Abstract: Cefiderocol is a new siderophore cephalosporin with activity against carbapenem-resistant gram-negative bacteria. Data on its clinical efficacy are limited to complicated urinary tract infections. We present a series of 3 patients successfully treated with cefiderocol for complicated health care–associated infections and review published case reports.